SENTRA PEDAGANG KECIL SEMANAN - Bianca Belladina; Martin Halim (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
According to Martin Heidegger, Dwelling in his book entitled "Building, Dwelling, Thinking" states that dwelling is a concept to inhabit or a unique way of being (dasein) in the world, namely to stay, wander (to wander) and survive (to linger). ). The concept of human habitation is more about survival. In general, humans cannot just stand by to survive, humans must work to meet their needs in survival. Then the question arises, "How do the lower class society, especially the traders live?" Seeing that small traders do not have land to sell so many of them sell on the side of the road. Semanan Small Traders Center is a place for small traders, especially the Semanan area, where traders who do not have land to sell now get land to sell so that traders do not need to  use the road again as a place to sell. In addition, this project seeks to answer the needs of the people around Semanan. The method used is Respond to Site - Contextualism. The design process in buildings is realized by a relationship with the environment around the needs of the surrounding community and the problems that exist around the site. Keywords: Dwelling; Semanan; Trader. AbstrakDwelling menurut Martin Heidegger dalam bukunya yang berjudul “Building, Dwelling, Thinking” meyebutkan bahwa dwelling sebagai sebuah konsep menghuni atau cara khas ada (dasein) di dunia yaitu untuk menetap (to stay), berkelana (to wander) dan bertahan hidup (to linger). Konsep berhuni manusia lebih ke bertahan hidup. Pada umumnya manusia tidak bisa hanya berdiam diri saja untuk bertahan hidup, manusia harus bekerja untuk memenuhi kebutuhannya dalam bertahan hidup. Lalu muncul pertanyaan “Bagaimana masyarakat kalangan bawah khususnya para pedagang berhuni?”. Melihat para pedagang kecil tidak memiliki lahan berjualan sehingga banyak dari mereka berjualan di pinggiran jalan. Sentra Pedagang Kecil Semanan merupakan wadah bagi para pedagang kecil khususnya daerah Semanan, dimana para pedagang yang tidak memiliki lahan untuk berjualan sekarang mendapatkan lahan untuk berjualan sehingga para pedagang tidak perlu memakai ruas jalan lagi sebagai tempat berjualan. Selain itu proyek ini berusaha untuk menjawab kebutuhan masyarakat sekitar Semanan. Metode yang digunakan yaitu Respond to Site – Contextualism proses desain pada bangunan diwujudkan dengan adanya hubungan dengan lingkungan sekitar kebutuhan masyarakat sekitar dan masalah yang ada disekitar tapak.